Peran Perpustakaan dalam Meningkatkan Kualitas Siswa dalam Bidang PAI di Era 4.0 - Burhani, A. Roisul; Arifin, Asif (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2023)
The 4.0 era brought major changes in various aspects of life, including education. Islamic Religious Education (PAI) is required to be adaptive and innovative in responding to the challenges of the times. One way to improve the quality of PAI in the 4.0 era is to maximize the role of libraries. This journal discusses the role of libraries in improving the quality of students in the field of PAI in the 4.0 era. This journal examines various aspects, such as the collection of PAI library materials available in the library, programs and services provided by the library to support PAI learning, library efforts in improving literacy and reading culture among students, and the impact of libraries on the quality of PAI learning. The results showed that libraries have a significant role in improving the quality of students in the field of PAI in the 4.0 era. The library provides quality learning resources, supports PAI learning, and enhances literacy and reading culture among students.